Aktualisasi Peran dan Tantangan Perguruan Tinggi Islam dalam Pencerahan dan Pencerdasan - Marjuni Marjuni (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2017)
This article elaborates the actualisation and challenges of Islamic Higher Education (PTAI). This study shows that PTAIs are not only a transfer or transfer of knowledge institution, but they are also able to support the students and the community in developing its potential. In the case of the FKTK of UIN Alauddin, this study shows that the faculty's response to social change with the effort to build intelligence and broaden the horizons, build a work ethic and apply a positive-active curriculum, and perform scientific integrations. It thus becomes crucial effort in order to prepare learners to become human resources with high academic ability and social sensitivity. The study, hence, recommends that the PTAIs should orient themselves to the future by applying the pillars of true education, namely: learning to know, learning to do, learning to be, and learning to live together.